Investigating the influence of polyacrylonitrile nanofiber thickness on particulate matter filtration performance from cigarette smoke - Wardiningsih , Dina; Aflaha , Rizky; Maharani , Chlara Naren; Triyana , Kuwat; Kusumaatmaja, Ahmad (Green and Sustainable Materials Society, 2024)
This study successfully fabricated polyacrylonitrile (PAN) nanofiber in various thicknesses as particulate matter (PM) filtration membranes using the electrospinning method. The PM source used was derived from cigarette smoke. Scanning electron microscopy (SEM) images and Fourier-transform infrared (FTIR) spectra are provided in the manuscript to observe the morphology and chemical composition of the fabricated nanofiber membrane. The thickness of the nanofiber was controlled based on the volume of the polymer solution, which was 4 mL, 6 mL, and 8 mL, and had a thickness of (52 ± 2) µm, (176 ± 27) µm, and (479 ± 38) µm, respectively (denoted as NF-4, NF-6, and NF-8 membranes). The results showed that the nanofiber membrane performed well against PM0.3, PM1, and PM2.5, with efficiency above 95.7%. Furthermore, it was observed that increasing the thickness of the nanofiber resulted in higher filtration efficiency. This trend is evident in the NF-8 membrane, which exhibited an efficiency of (97.9 ± 0.3)%, compared to only (95.7 ± 0.2)% for the NF-4 membrane against PM0.3. However, the pressure drop is also higher ((0.03 ± 0.005) kPa), which causes a trade-off in the quality factor (QF) of fabricated nanofiber performance as a PM filtration membrane.